2017
DOI: 10.1177/1066896917734915
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Ectomesenchymoma: Series Analysis of a Histologically and Genetically Heterogeneous Tumor

Abstract: Our analysis extends the histologic and molecular spectrum of these tumors and highlights their heterogeneity. The percentage of cases with alveolar rhabdomyosarcoma or primitive neuroectodermal-like tumor components suggests that these types of elements might be underreported. This study is also the first to demonstrate FOXO1 gene rearrangements in malignant ectomesenchymoma with alveolar rhabdomyosarcoma subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 17 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Similarly Huang et al observed a genetic link between these two tumors by demonstrating frequent HRAS mutations in MEM (5/7 cases) by Sanger sequencing overlapping with RAS mutations seen in an ERMS control group . The work by Griffin et al in addition supported the hypothesis that MEMs may represent a variant of RMS by demonstrating FOXO1 gene rearrangements by reverse transcription polymerase chain reaction in all three out of six cases of MEM with alveolar RMS histology . Additionally, Nael et al and Sorensen et al have recognized EWSR1 gene rearrangements (t(11;22)) in MEM in their respective works.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly Huang et al observed a genetic link between these two tumors by demonstrating frequent HRAS mutations in MEM (5/7 cases) by Sanger sequencing overlapping with RAS mutations seen in an ERMS control group . The work by Griffin et al in addition supported the hypothesis that MEMs may represent a variant of RMS by demonstrating FOXO1 gene rearrangements by reverse transcription polymerase chain reaction in all three out of six cases of MEM with alveolar RMS histology . Additionally, Nael et al and Sorensen et al have recognized EWSR1 gene rearrangements (t(11;22)) in MEM in their respective works.…”
Section: Discussionmentioning
confidence: 85%
“…7 The work by Griffin et al in addition supported the hypothesis that MEMs may represent a variant of RMS by demonstrating FOXO1 gene rearrangements by reverse transcription polymerase chain reaction in all three out of six cases of MEM with alveolar RMS histology. 21 Additionally, Nael et al 22 and Sorensen et al 23 have recognized EWSR1 gene rearrangements (t (11;22)) in MEM in their respective works. In contradiction to the above studies, recently Kleinschmidt-DeMasters et al found gene expression pattern of MEMs clustered closely with MPNSTs and not with RMS or EWS using microarray testing.…”
Section: Post-operativementioning
confidence: 99%
“…Though isolated reports of tumors diagnosed in adults have been published [ 6 , 7 ], the age of the patient in this report is exceptional. Similarly, whereas location of the primary tumor in the abdomen, pelvis, groin, perineum, paratesticular region, and vulva has been reported [ 2 5 ], ectomesenchymoma has not, to the best of our knowledge, been diagnosed as a primary uterine tumor to date. One possibility which cannot be entirely ruled out is that this tumor developed from a carcinocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients diagnosed with ectomesenchymoma are pediatric [ 2 5 ]. Though isolated reports of tumors diagnosed in adults have been published [ 6 , 7 ], the age of the patient in this report is exceptional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation